Bibliometric Analysis Of The Role Of Digitalization And Artificial Intelligence In The Development Of The Healthcare System - (:unkn) unknown (My University, 2025)
Digitalization and artificial intelligence (AI) are central to the transformation of healthcare systems, offering innovative solutions to improve efficiency, accessibility, and quality of care. This study adopts a bibliometric approach, analyzing academic publications indexed in Scopus and Web of Science between 2010 and 2025. The sample includes over 150 articles focused on the application of digitalization and AI in healthcare systems, particularly in developing countries. Using VOSviewer software, the study maps scientific collaborations, identifies emerging themes, and evaluates the influence of key publications. The results reveal increasing integration of digital and AI technologies, notably in telemedicine, hospital management, and AI-assisted diagnostics. The study concludes that these technologies have significant potential to address structural challenges in African healthcare systems, provided that investments are made in infrastructure, training, and governance. Recommendations are proposed to support inclusive and sustainable digital transformation in healthcare policy.Keywords: Bibliometric analysis, Digitalization, Artificial intelligence, Healthcare system, Innovative technologies, African development.
Keywords: African Research